2019
DOI: 10.1016/j.amsu.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Safe surgery in the elderly: A review of outcomes following robotic proctectomy from the Nationwide Inpatient Sample in a cross-sectional study

Abstract: Background As our nation's population ages, operating on older and sicker patients occurs more frequently. Robotic operations have been thought to bridge the gap between a laparoscopic and an open approach, especially in more complex cases like proctectomy. Methods Our objective was to evaluate the use and outcomes of robotic proctectomy compared to open and laparoscopic approaches for rectal cancer in the elderly. A retrospective cross-sectional cohort study utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…This shows an opportunity to increase MIS utilization in this population. Our findings are consistent with a study by Richards et al, who found a 39% increase in robotic use for proctectomy with a 6% decrease in the open approach in older persons between 2006 and 2013 24 . While the data are dated, this study supports the growing use of robotics overall and in the older people.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This shows an opportunity to increase MIS utilization in this population. Our findings are consistent with a study by Richards et al, who found a 39% increase in robotic use for proctectomy with a 6% decrease in the open approach in older persons between 2006 and 2013 24 . While the data are dated, this study supports the growing use of robotics overall and in the older people.…”
Section: Discussionsupporting
confidence: 92%
“…Robotic surgery has also been described as safe in the older person, with comparable minimally invasive benefits, but little study on utilization in this population. 24,[31][32][33] Older persons specifically benefit from MIS through decreased postoperative pain, resulting in less use of opioids and incidence of delirium, and faster return to normal function, resulting in quicker discharge, decreased nosocomial infection risk, and less discharge to place other than home. 29,[34][35][36] With the known benefits in the expanding aging population, further study to address the disparities in use is warranted.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations